Water management in the 21st century : problems and challenges - Abernethy, Charles L. (1997)
Suggests that the major challenge is to develop appropriate institutions for effective management, allocation and protection of the water resources of each basin and each aquifer, under the criteria of broadly-shared social objectives. Opines that if the challenge for the future is to develop effective hydrologically-based institutions for allocation and management of water, and to work through these institutions to curtail the growth of demand, the areas of need are namely. water statistics, water rights and water economics.